2022
DOI: 10.3390/pr10112438
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water, Nanoparticulate Silica and Dry Water on the Flow Properties of Cohesionless Sand

Abstract: Cement hydration within particle bed concrete 3D printing processes can be benefited by storing water in the otherwise dry aggregate bulk material. Additional water also has the advantage of acting as a source of passive cooling. However, even small amounts of liquid lead to detrimental effects on bulk properties, such as the flowability. For that reason, this study proposes implementing dry water (DW) in order to store large amounts of water in a bulk material of non-absorbent, coarse sand whilst maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We observed the avalanche phenomenon as a result of water bridge formation. Hamilton et al [13] and Herminghaus [14] found that cohesive nature of water bridge influenced single particles so that particles did not flow independently and caused avalanche phenomenon.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…We observed the avalanche phenomenon as a result of water bridge formation. Hamilton et al [13] and Herminghaus [14] found that cohesive nature of water bridge influenced single particles so that particles did not flow independently and caused avalanche phenomenon.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…Several patents report dry water as a suitable rapid cooling method for fire extinguishment or a retardant for certain reactions due to the release of the adsorbed water [23 -25]. By mixing dry water with aggregate particles, large amounts of water can be stored in the particle bed whilst maintaining its initial flow properties [26]. Consequently, suitable bulk properties can be ensured for a water-storing bulk material applied in SPI.…”
Section: Particle Coating With Dry Watermentioning
confidence: 99%
“…Produced variants were differentiated by their mass fraction of water at wH2O: 80%, 87%, 90%, and 95%. The mass fractions were chosen in accordance with [26].…”
Section: Passive Cooling By Coated Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive cooling strategies, such as aggregate functionalizing have already been investigated [12,13]. But also increasing the protruding distance between the welding point and the particle bed surface [12].…”
Section: Introductionmentioning
confidence: 99%